FDA Approved Drug Library Screening Identifies Robenidine as a Repositionable Antifungal - Mei, Yikun; Jiang, Tong; Zou, Yun; Wang, Yuanyuan; Zhou, Jia; Li, Jinyang; Liu, Lin; Tan, Jingcong; Wei, Luqi; Li, Jingquan; Dai, Huanqin; Peng, Yibing; et al. (Frontiers in Microbiology, 2020)
Due to the increasing prevalence of pathogenic fungal infections, the emergence of antifungal resistant clinical isolates worldwide, and the limited arsenal of available antifungals, developing new antifungal strategies is imperative. In this study, we screened a library of 1068 FDA-approved drugs to identify hits that exhibit broad-spectrum antifungal activity. Robenidine, an anticoccidial agent which has been widely used to treat coccidian infections of poultry and rabbits, was identified in this screen. Physiological concentration of robenidine (8 μM) was able to significantly inhibit yeast cell growth, filamentation and biofilm formation of Candida albicans – the most extensively studied human fungal pathogen. Moreover, we observed a broad-spectrum antifungal activity of this compound against fluconazole resistant clinical isolates of C. albicans, as well as a wide range of other clinically relevant fungal pathogens. Intriguingly, robenidine-treated C. albicans cells were hypersensitive to diverse cell wall stressors, and analysis of the cell wall structure by transmission electron microscopy (TEM) showed that the cell wall was severely damaged by robenidine, implying that this compound may target the cell wall integrity signaling pathway. Indeed, upon robenidine treatment, we found a dose dependent increase in the phosphorylation of the cell wall integrity marker Mkc1, which was decreased after prolonged exposure. Finally, we provide evidence by RNA-seq and qPCR that Rlm1, the downstream transcription factor of Mkc1, may represent a potential target of robenidine. Therefore, our data suggest that robenidine, a FDA approved anti-coccidiosis drug, displays a promising and broadly effective antifungal strategy, and represents a potentially repositionable candidate for the treatment of fungal infections.